Determinants of Financial Distress: A Portrait of the Post-Pandemic Transportation and Logistics Sector - Mario Stevando; Mahardika Shafa Azzumar (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to examine and analyze the relationship between Liquidity, Profitability, Firm Size, and Leverage on Financial Distress. Design/methodology/approach – This study uses quantitative data, with the sample consisting of companies in the energy, transportation, and logistics sectors listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The analysis technique used to test the hypothesis is multiple regression analysis using e-views 9 software. Findings – The research results indicate that Liquidity, Profitability, Firm Size, and Leverage have a negative but not statistically significant relationship with financial distress. These findings suggest that increases in Liquidity, Profitability, company scale, and Leverage tend to be followed by a decrease in Financial Distress risk, but this effect is not statistically strong enough during the 2022–2024 period. This indicates that in the post-pandemic recovery period and amid high global energy volatility, conventional financial ratios have limited explanatory power in predicting financial distress in companies in the energy, transportation, and logistics sectors. Research limitations/implications – This study is limited to companies in the energy, transportation, and logistics sectors listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period and examines only Liquidity, Profitability, Firm Size, and Leverage in relation to financial distress. The practical implication of this study is that conventional financial ratios should not be relied upon as standalone indicators for predicting financial distress in these sectors. For management and investors, the findings highlight the importance of complementing financial ratio analysis with external and sector-specific factors when assessing corporate financial resilience. JEL : G32, G33, L91, L94